CEO turnover and abnormal return: effects of the intensity of news disclosure in economic jornals - Matos, Ruben Mendes; Colauto, Romualdo Douglas (Revista de Administração da UFSM, 2020)
abnormal returns and CEO turnover motivations disclosures intensity based on the Efficient-Market Hypothesis (EMH) in its semi-strong form. Design/methodology/approach: A panel data of 65 events publicly traded Brazilian companies that have a Pension Fund among their shareholders, between 2010 and 2014 were used. Applying the Event Study methodology, the ordinary least-squares (OLS) multiple regression analysis was used to calculate the abnormal returns. The CEO turnover data were manually collected and systematically crosschecked, and content analysis were employed to identify its motivations. Spearman’s correlation measured the relation between motivation disclosure intensity and the abnormal returns. Findings: Results reveal a positive and statistically significance relationship between the abnormal return and the intensity of news reporting on CEO turnover. Practical Implications: The study it allows to understand whether the disclosure intensity of the CEOs turnover motivations affects the magnitude of the abnormal returns in firms of which the Pension Funds participate in the capital. Social Implications: The findings have one important implications in firms of which the Pension Funds participate in the capital. It makes possible to assess the Brazilian market behavior in the event of CEO's changing, as sophisticated and regulated institutional investors. Originality/Value: This study extended to disclosure intensity and returns literature by offering new evidence on the effect of CEO turnover motivations disclosures intensity on the market abnormal returns for Brazilian firms. Keywords: CEO turnover. Returns. Intensity of disclosure.